1985
DOI: 10.4269/ajtmh.1985.34.1132
|View full text |Cite
|
Sign up to set email alerts
|

Brugia Malayi: Vaccination of Jirds with 60Cobalt-Attenuated Infective Stage Larvae Protects against Homologous Challenge

Abstract: Vaccination of inbred jirds (Meriones unguiculatus) with 60cobalt radiation-attenuated Brugia malayi infective stage larvae (L3) protected against homologous challenge given either subcutaneously (sc) or by the intraperitoneal (ip) route. Groups of jirds vaccinated once sc with 75, 15 Krad L3 showed from 69% to 91% reduction in recovered worms after ip challenge infection compared to infection in non-vaccinated control jirds, while 75% reduction in mean worm burden was seen in jirds receiving sc challenge infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…This difference was significant (P Ͻ 0.05) by Whitney-Mann nonparametric statistics. The data reported here indicate greater than 70% protection in jirds against a challenge infection; this is substantially better than any previous filarial recombinant antigen reported and is in the range achieved by vaccination with radiation-attenuated larvae, 44 to 91% (35). Of the previously tested antigens, paramyosin has yielded disappointing results (20,21), while heat shock protein 70, myosin, and ␣1-type IV collagen have recently been shown not to stimulate protective immunity (30).…”
Section: Resultsmentioning
confidence: 63%
“…This difference was significant (P Ͻ 0.05) by Whitney-Mann nonparametric statistics. The data reported here indicate greater than 70% protection in jirds against a challenge infection; this is substantially better than any previous filarial recombinant antigen reported and is in the range achieved by vaccination with radiation-attenuated larvae, 44 to 91% (35). Of the previously tested antigens, paramyosin has yielded disappointing results (20,21), while heat shock protein 70, myosin, and ␣1-type IV collagen have recently been shown not to stimulate protective immunity (30).…”
Section: Resultsmentioning
confidence: 63%
“…Numerous studies have demonstrated that immunization with irradiated filarial larvae can lead to significant levels of protection from challenge infection (1,5,21,32,34,36,38). Le Goff et al (19) demonstrated that in the L. sigmodontis model this killing is very rapid, with larval destruction occurring within the first 2 days following challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from several animal models in which the life cycles of Brugia species are reliably maintained indicates that a moderate degree of resistance to infection can be achieved by immunization with live, radiation-attenuated infective L3's (35,36). However, the immunologic or biochemical nature of any protective antigens effecting immunity in these models has yet to be elucidated, a fact emphasizing the need for multiple alternative approaches.…”
Section: Antigen Recognition By Igg Antibody In Ens and Mfsmentioning
confidence: 99%